(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
During the last decades there has been a constant increase in a number of allergic diseases all over the world. The high urgency of the problem of allergy prevention is due to the fact that the frequency of occurrence of allergies, especially among young people, is rapidly increasing year by year. This research paper is devoted to one of the most urgent and actual problems of our time – the problem of preventing the appearance of food allergies among young people. As part of the study, the authors consider the concept and essence of food allergy, the main causes and factors that provoke its occurrence in the student age category, and offer the main methods of preventing this disease using recreational physical education. The research paper presents the results of a sociological study conducted along with the students of the Medical Faculty of the Gulistan State University of the Republic of Uzbekistan